Multiple use of an industrial‐distributed control system in control engineering education. Issue 2 (4th February 2011) - Dittmar, Rainer; Kahlcke, Thomas
Abstract The paper demonstrates how a four‐tank laboratory process equipped with a modern distributed control system (DCS) is used in different control engineering laboratories for the undergraduate and graduate levels. This includes the utilization of commercial tools for DCS engineering as well as the design and commissioning of traditional and advanced control solutions. Using the same pilot plant and control system in different modules lowers the costs, allows the reutilization of results and enables an efficient laboratory organization. It also supports the process of learning the inner context of different process control related subjects. © 2011 Wiley Periodicals, Inc. Comput Appl Eng Educ 21: 313–321, 2013